Diseminasi Teknologi Mesin Pengupas Kulit Ari Kacang Hijau Sistem Roller Terbarukan Di Desa Karangpaing Kecamatan Penawangan Kabupaten Grobogan - Achmad Buchori; Sigit Ristanto; Yuris Setyoadi; Fafa Nurdyansyah (Journal of Dedicators Community, 2020)
Karangpaing Village is a green bean farming center. However, post-harvest processing is still manual so that production is small. This activity of disseminating technology products to the community aims to improve the welfare of citizens by increasing the production capacity of green beans with a renewable roller system, as well as increasing the value of their sales and marketing. This service method includes interviews, observation, socialization, discussion, practice and question and answer. The outputs generated from this activity include Karangpaing green bean farmers who can operate pulping machines, diversify mung bean products, carry out good financial management and marketing. This activity has been handed over to 5 units of mung bean epidermis peeler and has been trained to process green beans into several processed variations such as green bean extract milk, bakpia, bakpao and others, so that the residents are very enthusiastic.